Prefrontal cortex activity during virtual obstacle avoidance and distracted walking: A methodological proof of concept using augmented reality and functional near-infrared spectroscopy - L. Maureen Krelove; Anthony Machula; Lauren E. Sergio; George Mochizuki (PLoS ONE, 2025)
Introduction There is an established interplay between gait and attention allocation. Attention during walking is important to reduce instability, process environmental stimuli, and perform simultaneous tasks. It is of critical importance to consider how attention modulation during dual-tasking influences prefrontal cortex (PFC) activity and gait characteristics. However, paradigms probing this relationship are often limited in realism and must balance mobility challenges with practicality. This protocol introduces a novel methodology combining functional near-infrared spectroscopy (fNIRS) and augmented reality (AR) in a complex gait dual-task to validate the use of virtual obstacles to probe for a cortical indicator of altered attention during distracted walking. Materials and methods This methodological development study investigated 11 healthy adults (mean age 50.9 ± 5.8 years, 5 female) in an obstacle navigation cognitive-motor dual-task combining fNIRS and AR during navigation of realistic AR-projected 3D virtual obstacles and physical obstacles. The distraction task involved a 5-word recall from a mimicked phone call. Participants performed six experimental tasks: walking; walking + distraction; walking + obstacles (both physical and virtual); and walking + obstacles (both physical and virtual) + distraction. Results Intraclass correlations ranged from 0.563 to 0.886 for oxyhemoglobin (O2Hb) ratios and gait velocity between virtual and physical obstacles, demonstrating moderate-to-good consistency between methods. Proportional bias in the Bland-Altman plots was observed for O2Hb. Participants also demonstrated task-dependent modulation of gait and PFC activity in response to dual task conditions in both tasks. Conclusions This combination of technologies elicited task-dependent modulation in PFC activity and gait behaviours in healthy adults, confirming the efficacy of AR-projected obstacles in a cognitive-motor dual-task paradigm. Based on these outcomes, it is likely that this experimental approach will be useful in probing cortical activity changes associated with dual-tasking to inform the relationship between mobility and cognition and characterize behavioural and neural markers of functional mobility.